Exploration of Energy-Saving Chilling Landscape Design Based on Algo for Group Intelligence - Zhuo Li (Journal of Function Spaces)
Due to the influence of regional climatic conditions, the development of cold ecological tourism agricultural park in the north is slow, its landscape planning and design research lags behind, and there are still some problems. With the development of electronic computers, the previously unachievable optimization of engineering structures is now possible, while the traditional optimization methods cannot meet the requirements of modern computing due to the implementation constraints. The emergence of algo for group intelligences has made some applications of engineering structural optimization possible. Group intelligence is the characteristic of a system in which the collective behavior of low-level individuals interacting locally with their environment forms an overall pattern of consistent functions. This paper presents a study of energy-efficient cold landscape design based on algo for group intelligences and analyzes the problems that arise in the ecological landscape design of cold urban settlements. Then countermeasures are proposed to solve the problems. The linear model is replaced by the determination of the weight of the evaluation index of the energy-saving design of frozen landscape. And take it as a new migration model. Then, based on the weight of the evaluation index, the group algorithm analysis in landscape design is proposed, which is a generalized definition of the standard model. The experimental results show that the algo for group intelligence outperforms another algorithm in terms of solving ability to the extent that the average optimization ability is improved by 13.45%, so the algo for group intelligence demonstrates its superior ability to take into account both local and global search. Therefore, the use of algo for group intelligences to build an energy-efficient society is a necessary path for China’s development, and the construction of energy-efficient gardens is an important part of building an energy-efficient society, and the application of energy-efficient concepts to modern landscape design is an inevitable trend in the development of urban landscaping.